Women and the contradictions of agrarian capitalism - Saffioti, Heleieth; Ferrante, Vera Lúcia Silveira Botta (Universidade Estadual Paulista / UNESP, 2007)
The article deals the transition from familial rural economy to wage labor. The status of women goes down ad they loose also economic functions.